The role of additional correction methods of insufficient adherence to treatment for effective blood pressure control in patients with resistant arterial hypertension - Voloshyna, O.; Zbitnieva, V.; Busel, S.; Chaika, A.; Samorukova, V.; Dychko, T. (Journal of Education, Health and Sport, 2016)
Voloshyna O., Zbitnieva V., Busel S., Chaika A., Samorukova V., Dychko T. The role of additional correction methods of insufficient adherence to treatment for effective blood pressure control in patients with resistant arterial hypertension. Journal of Education, Health and Sport. 2016;6(12):857-865. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.252818 http://ojs.ukw.edu.pl/index.php/johs/article/view/4184 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.12.2016. Revised 20.12.2016. Accepted: 25.12.2016. УДК 616.12-008.331.1-036.8 THE ROLE OF ADDITIONAL CORRECTION METHODS OF INSUFFICIENT ADHERENCE TO TREATMENT FOR EFFECTIVE BLOOD PRESSURE CONTROL IN PATIENTS WITH RESISTANT ARTERIAL HYPERTENSION O. Voloshyna, V. Zbitnieva, S. Busel, A. Chaika, V. Samorukova, T. Dychko Odessa National Medical University, Ukraine Abstract The article considers the results of applying the different correction methods of insufficient adherence to treatment in patients with resistant and pseudo-resistant arterial hypertension on the background of the optimization of antihypertensive therapy in the effective blood pressure control by a doctor and a patient. Keywords: resistant hypertension, pseudo-resistant hypertension, uncontrolled blood pressure, adherence